(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the use of dental services by pediatric patients with Down Syndrome according to caregivers. Methodology: A cross-sectional study was carried out at the Fundação Centro Integrada de Support to the Disabled (FUNAD), in João Pessoa-PB. The sample consisted of 49 caregivers of patients with Down syndrome, between 0 and 15 years old. Socioeconomic and satisfaction data about the service offered were collected using a form designed in accordance with the research objectives. Results: It was observed that 83.7% of the patients have already been to the dentist, more frequently in the Basic Health Unit (47.5%). 97.5% of the caregivers were satisfied with the assistance received in the visits. The professionals were considered prepared by 75% of the caregivers. The use of physical stabilization was necessary in 50% of the cases. Most consultations were performed by dentists who were not specialized in Patients with Special Needs (62.5%) and the offices were not adapted (60%). Final considerations: The use of dental services by the patient and the caregiver must be considered purposes to be achieved by any health service, as they represent a monitoring of the actions offered in the eyes of those who seek them.